Kualitas Pelayanan Penanganan Stunting di Puskesmas Waiwerang Kecamatan Adonara Timur Kabupaten Flores Timur - Ola, Yosefina Ese; Niga, Jacoba D.; Pah, Theny I. B. Kurniati (Program Pasca Sarjana Universitas Garut, 2024)
Currently, Indonesia is facing various problems in the health sector, one of which is the problem of nutrition (stunting). Stunting is characterized by the child's length or height being below the standards set by the minister administering government affairs in the health sector.This research aims to analyze the quality of stunting treatment services and the factors that cause stunting at the Waiwerang Community Health Center, East Adonara District. This research discusses 5 indicators, namely direct evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance, concern (emphaty). Data collection techniques were carried out using observation, interviews and documentation studies and using triangulation techniques in analyzing the data. The results of the research show that the cause of the low quality of services for handling stunting is due to indicators that do not comply with service standards, namely the dimensions of physical evidence because the physical facilities of posyandu are limited and not all posyandu have anthropometric kits. Apart from that, the reliability dimension is due to the absence of special treatment from midwives when children experience fever or heat as a side effect of vaccination and the anthropometric kit which sometimes has error so that the accuracy of the measurement results is doubtful.